Restructuring Indonesia’s Directorate General of Intellectual Property Into an Autonomous Agency to Strengthen Valuation Function and Economic Utilization of Intellectual Property in Indonesia - Muhammad Insan Kamil (Leges Privatae, 2025)
This research examines the urgency of restructuring the Directorate General of Intellectual Property (DGIP) into an autonomous body to strengthen the valuation functions and optimize the economic utilization of intellectual property in Indonesia. Intellectual Property (IP) plays a strategic role in driving innovation and knowledge-based economic growth. However, IP governance in Indonesia continues to face challenges, including weak institutional capacity, low commercialization rates of innovation outputs, and an inefficient valuation system. The Directorate General of Intellectual Property (DGIP), as the national authority responsible for IP protection and administration, currently lacks an adequate institutional structure to address these challenges optimally. This study examines three main issues: (1) the characteristics of current IP governance in Indonesia and its challenges in valuation and economic utilization; (2) the effectiveness of DGIP’s institutional framework in supporting IP valuation and commercialization; and (3) an ideal institutional restructuring model to transform DGIP into an autonomous body. The research combines normative juridical approaches, qualitative data analysis, and comparative studies of IP institutional models in South Korea, Japan, the United States, the European Union, China, Singapore, Saudi Arabia, and Egypt. Findings reveal that DGIP’s current administrative and bureaucratic structure limits flexibility in resource management, innovation ecosystem development, and IP commercialization. The study recommends restructuring DGIP into a Public Service Agency (PSA the Indonesian term being Badan Layanan Umum) to strengthen valuation functions and optimize the economic utilization of IP. This model is expected to enhance public service efficiency, encourage private sector engagement, and foster cross-sectoral synergy in developing a knowledge-based economy.